Risk Indicators in Business Processes in Creative Economy to Improve Product Competitiveness - Sulistiyowati, Wiwik; Rodiyah, Isnaini; Astutik, Ikaratna Indra (Tibuana, 2022)
In the era of the industrial revolution 4.0, we are in an age where the concept of an online system (cyber-physical system), the concept of the internet for everything or IoT (Internet of Things), and the concept of networking (networks). The creative economy must be the backbone of the Indonesian economy. In the era of the industrial revolution 4.0, we are in an age where the concept of an online system (cyber-physical system), the idea of the internet for everything or IoT (Internet of Things), and the idea of networking (networks). The creative economy must be the backbone of the Indonesian economy. This research aims to measure risk so that risk indicators in business processes in the Creative Economy will be known. The method of carrying out this research is by distributing questionnaires or questionnaires. Then do validation and reliability and calculate the indicators that have the highest level of risk. The results of this study are the demand risk variable with an indicator of the presence of business competitors with a value of 3.2 points which means that the risk is very high faced by business actors, and the raw material risk variable with an indicator of insufficient supply of raw materials with a value of 2.93 which means high risk faced by business actors.